The Quality of Scientific Papers of Undergraduate Students in Regional Language and Literature Studies Lectures Before and After Using ChatGPT as a Writing Tool - Ari Wulandari; Arif Budiman; Tri Ratna Herawati; Primasari Wahyuni; Diaz Danu Setyawan (Script Journal: Journal of Linguistics and English Teaching, 2026)
Background:  This study addresses the growing use of ChatGPT in academic writing. Grounded in constructivism, the study investigates changes in the quality of scientific papers produced by undergraduate students in the Regional Language and Literature Studies course at University “A” before and after the use of ChatGPT as a writing support tool. Methodology:  A quasi-experimental pretest–posttest design using document analysis was applied. The data consisted of 30 student papers written before and after ChatGPT use. Assessment covered five aspects: ideas, organization, grammar, diction, and spelling. Findings:  The findings indicate substantial improvements in students’ scientific papers after the use of ChatGPT. The mean writing score increased from 77.9 before ChatGPT-assisted revision to 89.0 after revision, and 27 of the 30 papers improved to the excellent category. The strongest improvements were observed in organization, grammar, diction, and spelling, whereas gains in idea development were comparatively more modest. Conclusion:  The findings suggest that ChatGPT-assisted revision can enhance the technical quality of students’ scientific writing. However, lecturer guidance remains necessary to support critical thinking, independent analysis, and the responsible use of generative AI in academic writing. Originality:  This study contributes empirical evidence on changes in the quality of students’ scientific writing associated with ChatGPT-assisted revision within the context an undergraduate language and literature course.